ELECTROCHEMICAL pH-STAT AS ACIDITY MONITORING SYSTEM IN HIGH IONIC STRENGTH SOLUTIONS. I. DESIGN CHALLENGES AND PRELIMINARY RESULTS - BOGDAN, Gabriele-Mario; DORNEANU, Sorin-Aurel (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Quantifying acidity has evolved from early attempts in the 1300s to the modern glass electrode pH sensor, which is difficult to implement for monitoring acid concentration in highly saline solutions. In this study a membrane-based filter-press electrochemical reactor functioning as a pH-stat that correlates current with acid concentration was tested. The behavior of HBr in KBr solutions was characterized, after which spectroscopic measurements of Alizarin Red S provided calibration curves used to validate glass electrode data. Reactor design principles and challenges were discussed, after which its behavior under non-polarized and polarized conditions was studied, concluding with two pH-stat tests, where different HBr concentrations were simulated by changing the acid molar flow rate, with pH values corroborated by spectroscopic measurements. A linear relationship was demonstrated between steady state current and acid molar flow rate. Imperfect membranes resulted in systematic errors between the amount of acid introduced and that neutralized. Preliminary results confirmed the feasibility of the electrochemical cell as an acid monitoring system, with future upgrades including PID control and design optimization.